Influence of hexose-phosphates and carbon cycling on sucrose accumulation in sugarcane spp. - Van der Merwe, Margaretha Johanna (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Genetics. Plant Biotechnology))--University of Stellenbosch, 2005.